Mechanism of discrimination of isoleucyl‐tRNA synthetase against nonproteinogenic α‐aminobutyrate and its fluorinated analogues. (18th September 2019) - Zivkovic, Igor; Moschner, Johann; Koksch, Beate; Gruic‐Sovulj, Ita
Abstract : Isoleucyl‐tRNA synthetase (IleRS) is a paradigm for understanding how specificity against smaller hydrophobic substrates evolved in both the synthetic and editing reactions. IleRS misactivates nonproteinogenic norvaline (Nva) and proteinogenic valine (Val), with a 200‐fold lower efficiency than the cognate isoleucine (Ile). Translational errors are, however, prevented by IleRS hydrolytic editing. Nva and Val are both smaller than Ile by a single methylene group. How does the removal of one additional methylene group affects IleRS specificity? We found that the nonproteinogenic α‐aminobutyrate (Abu) is activated 30‐fold less efficiently than Nva and Val, indicating that the removal of the second methylene group comes with a lower penalty. As with Nva and Val, discrimination against Abu predominantly originated from a higher K M . To examine whether increased hydrophobicity could compensate for the loss of van der Waals interactions, we tested fluorinated Abu analogues. We found that fluorination further hampered activation by IleRS, and even more so by the evolutionary‐related ValRS. This suggests that hydrophobicity is not a main driving force of substrate binding in these enzymes. Finally, a discrimination factor of 7100 suggests that IleRS is not expected to edit Abu. However, we found that the IleRS editing domain hydrolyzes Abu‐tRNA Ile with a rate of 40 s −1 and the introduction of fluorine did not slow down the hydrolysis. This raises interesting questions regarding the mechanism of specificity of the editing domain and its evolution. Understanding what shapes IleRS specificity is also of importance for reengineering translation to accommodate artificial substrates including fluorinated amino acids. Enzymes: Isoleucyl‐tRNA synthetase (EC 6.1.1.5 ), leucyl‐tRNA synthetase (EC 6.1.1.4 ), valyl‐tRNA synthetase (EC 6.1.1.9 ). Abstract : Isoleucyl‐tRNA synthetase (IleRS) incorporates isoleucine into proteins. Here, we show that IleRS can activate and transfer to tRNA Ile nonproteinogenic α‐aminobutyrate and its synthetic fluorinated analogues. However, α‐aminobutyrate recognition was strongly impaired, and loss of van der Waals interactions was not compensated for, by increased substrate hydrophobicity. Interestingly, all misacylated tRNA Ile s were efficiently edited. This raises interesting questions about the mechanism of specificity and evolution of the editing domain.